Surgical treatment of a giant left ventricular aneurysm- A case report - Schaitza,Gustavo Alves (2014)
An aneurysm of the left ventricle is a complication of acute myocardial infarction. We report a case of a giant aneurysm of the left ventricle after myocardial infarction in a 59 year-old male patient. The surgery to correct the aneurysm was performed with the use of cardiopulmonary bypass under normothermia. A bovine pericardial patch was used for the geometric reconstruction of the ventricular wall affected by the aneurysm. After the procedure, echocardiography and magnetic resonance imaging revealed improvement in left ventricular ejection fraction and volume reduction.